Catividade marcária como vetor da responsabilidade civil empresarial nas cadeias de fornecimento de bens - Cabral, Andre Luiz Cavalcanti (2016)
The doctoral thesis entitled "Trademark Captivity as a vector of corporate civil liability in the suppliers of goods network" linked to the area of research "Social, Economic Regulation and Development", aims to propose a new theoretical and practical legal model of corporate civil liability based on brand. The proposal is the result of research that addresses issues related to; Law of Industrial Property, Development Law, Marketing, Commercial Law and Civil Liability to propose a new form of liability using the mark as a vector. The brand is an asset, increasingly valued in the business world for its attraction power in the consumer market. The monopoly of economic exploitation of a distinctive sign has been secured by legal systems for centuries. It is recognized that the trademark is an important factor influencing the choices made by consumers. So this consumer attractiveness, which is increasingly implicit, can be considered one of the vantage points of the phenomenon called Trademark Captivity. Economic globalization makes businessmen seek new contractual legal relations, this results in multiple related captive contracts, among others, a revelation of the spread of new ways of acting in the market. On the other hand, economic agents create non-contractual models of relations between themselves, forming dynamic and flexible network supply. However there is a clear difficulty in identifying the contours of these relationships and their legal consequences, especially about civil liability. The problem gets worse when we observe that the current society is a society of multi-level risks. The challenge of investigating the possibility of the brand becoming a vector of corporate civil liability for network suppliers relationships by trademark sharing, meets the claim of compensatory protection for various damages to consumers. This work aims to contribute to the perspective of this study and will investigate which legal consequences of trademark captivity on civil liability for brand sharing should be applied. Also, the thesis structures a number of legal bases for the application of trademark captivity in the civil liability phenomenon. From the assumptions to be studied, one can understand a new form of civil liability for business corporations, an adjustment to the constitutional and economic order which can serve to regulate business activity grounded in fundamental principles such as the social duty of property. The trademark captivity itself is an important instrument for enforcing rights for consumers who now have one more tool in the quest for compensatory protection against exposure to risks in network suppliers.